The Incidence of Gastrointestinal Helminthiasis in Etawa Crossbred Goat in Etawa Farm Jombang - Dwi Novita Sari; Tri Wahyu Suprayogi; Djoko Legowo; Siti Eliana Rochmi (Universitas Airlangga, 2020)
Background: Goat is one type of small ruminant that has a contribution to supporting the development of livestock and is an alternative to meet the needs of animal protein in Indonesian society. The current goat raising system is still carried out by being caged or semi-grazed. In this maintenance system, goats are very susceptible to parasitic diseases, especially those caused by the digestive tract worms. Gastrointestinal worms are a significant problem in livestock, especially small ruminants that cause health problems, such as diarrhea, weight loss, and decreased appetite. Purpose: To determine the percentage and types of digestive tract helminths in Etawa crossbred goats by age. Method: 30 feces samples from Etawa crossbred goats were collected for laboratory examination using native, sedimentation, and flotation methods. Result: From the microscopic examination, it was found that the prevalence of gastrointestinal helminthiasis was 56.6%. Also, the type of worm eggs found in the feces samples from Etawa crossbred goats were Cotylophoron cotylophorum, Moniezia benedeni, Oesophagostomum columbianum, Strongyloides papillosus, Haemonchus contortus, Trichostrongylus sp., and Trichuris globulosa.